The Consumers’ Level of Satisfaction With the Service Quality of Kopdit Sumber Kasih Tangeb in Abianbase, Gianyar, Bali - I Made Yogiarta; I Putu Agus Dedy Pranata (Jurnal Ekonomi dan Bisnis Jagaditha, 2019)
The aim of this research is to analyze the level of customers’ satisfaction with service quality and the factors prioritized for improvement, so as to increase the consumers’ satisfaction at the Kopindit Sumber Kasih Tangeb in Abianbase Village. The research sample was determined with the solvin method as many as 97 consumers. The results of data analysis showed that, the average index of the consumers’ satisfaction on the Sumber Kasih Tangeb Credit Union in Abianbase Village was -811,595 where the score was between -1,036,648 to 648,432 which means that consumers at Kopdit Sumber Kasih Tangeb in Abianbase were quite satisfied with the quality of their services. Based on the analysis of the level of importance of performance (importance performance analysis) of the 97 consumers studied and viewed from the level of suitability and complaints of consumers, it is known that the factors that need to be given the highest priority from Kopdit Sumber Kasih Tangeb in Abianbase Village are services that meet the promise with a suitability level 41,9% while the factor that needs to get the final improvement is a comfortable waiting room with a suitability level of 121%.